Consanguinity, cardiac arrest, hearing impairment, and ECG abnormalities: counselling pitfalls in the Romano-Ward syndrome. Issue 4 (April 1993) - Reardon, W; Lewis, N; Hughes, H E
Abstract : Genetic counselling in the autosomal dominant condition of the Romano-Ward syndrome might be assumed to be relatively straightforward. The problems posed by consanguinity, deafness, and subclinical gene carriers in a pedigree with this condition have caused us to reevaluate this view. The diagnostic and management difficulties which may attend this potentially fatal condition are highlighted by our experience with this family.